Precision public health alliances as a model and method for community engagement - McGladrey, Margaret L.; Lacy, Mary Elizabeth; McQuerry, Kristen; Hogg-Graham, Rachel; Slavova, Svetla; Clear, Emily R.; Heier, Kory; Phan, Caitline; Hall, Megan; Parker, Ryan; Keeton, Mindy; Sword, Jennifer; et al. (Frontiers in Public Health, 2025)
Using precision analytics approaches with population health data helps identify localized patterns of social determinants and comorbidities, supporting the design of tailored interventions. The University of Kentucky College of Public Health (UKCPH) and UK King’s Daughters (UKKD) have partnered to create a Precision Public Health Alliance (PPHA) applying precision analytics to UKKD electronic health records (EHR) as well as secondary datasets to map social, demographic, and clinical comorbidity factors onto colorectal cancer (CRC) screening data in UKKD’s rural service area (the northeastern Kentucky counties of Boyd, Carter, Greenup, and Lawrence and southeast Ohio county of Lawrence). In addition to UKKD and UKCPH clinicians and researchers, PPHA includes a community-based Action Team of local social services, behavioral health, and public health agencies and Cooperative Extension agents responsible for translating findings into quality improvement priorities. In Fall 2024, UKKD and UKCPH developed a statistical analysis plan to examine the interplay of social, geographic, and clinical factors associated with CRC screening rates, which is a UKKD quality improvement priority. Findings from this analysis of EHR and secondary county-level data and a summary of UKKD’s existing quality improvement efforts related to CRC screening were presented to the Action Team in March 2025. The first meeting of the Action Team demonstrated initial proof-of-concept that PPHA approaches can catalyze community-based practice improvements. Immediately after the meeting with UKCPH support, the local health department and community mental health center pursued adoption of UKKD stool-based screening strategies and UKKD created a simple workflow for receiving referrals from community-based partners. This community case study contributes to community engagement with initial findings and best practices for PPHA of healthcare systems, local public health departments, and social services agencies to analyze population health trends in order to target quality improvement needs and co-design place-based, cross-sector strategies to address them with evidence-based practices. This replicable PPHA pilot in rural Kentucky and Ohio is an innovative method and model for how to engage communities most effectively in identifying and taking action to improve their chief health concerns.